2021
DOI: 10.1590/0001-3765202120201952
|View full text |Cite
|
Sign up to set email alerts
|

The 100,000 most influential scientists rank: the underrepresentation of Brazilian women in academia

Abstract: Despite the progress observed in recent years, women are still underrepresented in science worldwide, especially at top positions. Many factors contribute to women progressively leaving academia at different stages of their career, including motherhood, harassment and conscious and unconscious discrimination. Implicit bias plays a major negative role in recognition, promotions and career advancement of female scientists.Recently, a rank of the most infl uential scientists in the world was created based on seve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…Thus, the diagnosis of the Brazilian Entomology scenario presented here revealed that female researchers do not publish less, but they appeared less in the academic scenario probably due to its structure. Not only can we observe this pattern at the ABC but at the 100,000 most influential scientists in the world [ 41 ], where only 0.25–0.30% are Brazilians [ 25 , 41 , 42 ] and, among these, only 11% of those were women [ 25 ]. Also, around 1% of scientists worldwide among the 100k most influential were assigned in the subfield of Entomology and, among them, seven are Brazilians, all male researchers [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the diagnosis of the Brazilian Entomology scenario presented here revealed that female researchers do not publish less, but they appeared less in the academic scenario probably due to its structure. Not only can we observe this pattern at the ABC but at the 100,000 most influential scientists in the world [ 41 ], where only 0.25–0.30% are Brazilians [ 25 , 41 , 42 ] and, among these, only 11% of those were women [ 25 ]. Also, around 1% of scientists worldwide among the 100k most influential were assigned in the subfield of Entomology and, among them, seven are Brazilians, all male researchers [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scientific community constantly considers as influential a scientist who publishes a high number of articles, with high number of citations [ 25 ]. However, the number of papers and of citations, often equalized with scientific impact, has been repeatedly shown not to reflect the quality of the scientific endeavor [ 12 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While academics state that they are not gender biased, research shows that both women and men are biased against women in this environment (Roper, 2019). Bias against women are also evident in metrics used to evaluate academics, from impact factors to reference letters (Fortin et al, 2021), which in turn hurts women's recognition and prestige (Oliveira et al, 2021). Most of the time, this bias can be implicit, that is, not explicitly perceived.…”
Section: Introductionmentioning
confidence: 99%